2022
DOI: 10.3390/ijms23147796
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Calcium Supply Dependent Calcium Balance, Bone Calcification and Calcium Isotope Ratios in Rats

Abstract: Serum calcium isotopes (δ44/42Ca) have been suggested as a non-invasive and sensitive Ca balance marker. Quantitative δ44/42Ca changes associated with Ca flux across body compartment barriers relative to the dietary Ca and the correlation of δ44/42CaSerum with bone histology are unknown. We analyzed Ca and δ44/42Ca by mass-spectrometry in rats after two weeks of standard-Ca-diet (0.5%) and after four subsequent weeks of standard- and of low-Ca-diet (0.25%). In animals on a low-Ca-diet net Ca gain was 61 ± 3% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Dietary Ca deficiency improves the Ca retention or absorption in both mammals ( Centeno et al., 2009 ; Hernandez-Becerra et al., 2020 ; Rott et al., 2022 ) and birds ( Gilbert, 1983 ; Gautier et al., 2017 ), which is adaptively required for maintaining blood Ca concentration. The current results also showed that the Ca retention ratio was up from 53.12% to 74.88% when the dietary Ca content went from 3.7% down to 2%, which meant that most Ca was compensatively absorbed in hens fed the low Ca diet.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary Ca deficiency improves the Ca retention or absorption in both mammals ( Centeno et al., 2009 ; Hernandez-Becerra et al., 2020 ; Rott et al., 2022 ) and birds ( Gilbert, 1983 ; Gautier et al., 2017 ), which is adaptively required for maintaining blood Ca concentration. The current results also showed that the Ca retention ratio was up from 53.12% to 74.88% when the dietary Ca content went from 3.7% down to 2%, which meant that most Ca was compensatively absorbed in hens fed the low Ca diet.…”
Section: Discussionmentioning
confidence: 99%